Don't forget, God bless our troops - Biden, Jill.; e (New York : Simon & Schuster Books for Young Readers, 2012)
Five-year-old Natalie, misses her dad who is off to war, she sends him her artwork, packages of treats, and prays for him.
2.5
K-3
510L
Keywords: Children of military personnel -- United States -- Juvenile literature; Families of military personnel -- United States -- Juvenile literature; Soldiers -- Family relationships -- United States -- Juvenile literature; Children of military personnel; Families of military personnel; Soldiers